Congenital vascular hamartoma in the spinal cord of a neonatal foal - Paz, Tatiana; Henderson, Eileen; Asín, Javier; Streitenberger, Nicolas; Uzal, Francisco A. (Brazilian Journal of Veterinary Pathology, 2025)
A three-day-old Arabian filly with a history of not being able to stand unassisted after birth and lack of control over the right front and right hind limbs. The filly had inadequate proprioceptive responses, with absent pain/withdraw answer, and failed to respond to medical therapy. Due to the poor prognosis, euthanasia was elected, and a full necropsy was performed.